Overcoming Biological Barriers With Block Copolymers-Based Self-Assembled Nanocarriers. Recent Advances in Delivery of Anticancer Therapeutics - Torres, Jazmin; Dhas, Namdev; Longhi, Marcela; García, Mónica C. (Frontiers in Pharmacology, 2020)
Cancer is one of the most common life-threatening illness and it is the world's second largest cause of death. Chemotherapeutic anticancer drugs have many disadvantages, which led to the need to develop novel strategies to overcome these shortcomings. Moreover, tumors are heterogenous in nature and there are various biological barriers that assist in treatment reisistance. In this sense, nanotechnology has provided new strategies for delivery of anticancer therapeutics. Recently, delivery platforms for overcoming biological barriers raised by tumor cells and tumor-bearing hosts have been reported. Among them, amphiphilic block copolymers-based self-assembled nanocarriers have attracted researchers worldwide owing to their unique properties. In this wrok, we addressed different biological barriers for effective cancer treatment along with several strategies to overcome them by using ABC-based self-assembled nanomaterials, with special emphasis in those that have the ability to act as responsive nanocarriers to internal or external environmental clues to trigger release of the payload. These nanocarriers have shown promising properties to revolutionize cancer treatment and diagnosis, but there are still challenges for their successful translation to clinical applications.